A New Miniature Micro-Strip Two-Layer Band-Pass Filter Using Aperture-Coupled Hairpin Resonators - Chami, N.; Saigaa, D.; Djaiz, A. (Engineering, Technology & Applied Science Research, 2022)
The goal of this project was to provide novel band-pass filter design techniques for mobile communications, which allow a significant reduction in the size of the filters produced. The novelty comes from the transformation of the single layer technique into a double layer technique by inserting coupling slots in a common mass plane. Because of their tiny size, these filters are suitable candidates for integration into mobile communication systems. Indeed, when compared to the dimensions of a single-layer planar filter, the multilayer construction allowed us to reduce the size of the filter by more than 40%. Five U-shaped hairpin resonators were placed on two micro-strip layers in the planned filter. Two apertures etched on a common ground plane positioned between the two layers allow varied couplings between the upper and bottom layer resonators. A five-pole hairpin band-pass filter was created as a result.